The Effect of Additional Phytase Enzymes with Different Dosages on Feed to Growth, Feed Efficiency, and Survival of Snakehead Fish (Channa striata) - Rinda Julita Pahlevie; Mohamad Amin; Retno Cahya Mukti (Department of Aquaculture, 2023)
Snakehead (Channa striata) is a type of freshwater fish. Artificial feed generally contains animal and vegetable protein sources. The use of vegetable protein in snakehead has been carried out. However, it is still not optimal due to the presence of phytic acid in vegetable materials which makes fish unable to digest food properly. Therefore, it is necessary to add a phytase enzyme to hydrolyze phytic acid. This study aims to determine the effect of adding phytase with different doses to artificial feed on growth, protein efficiency ratio, feed efficiency, and survival of snakehead. This study used a completely randomized design (CRD) which consisted of four treatments and three replications, namely P0 (without the addition of phytase), P1 (addition of phytase 30 mg/100 g vegetable material), P2 (addition of phytase 50 mg/100 g vegetable material), P3 (addition of phytase 70 mg/100 g vegetable material). The size of the fish used in this study was 3-4 cm, with a stocking density of 2 fish/L fish. The rearing of the study was 30 days. The results showed that the addition of phytase 70 mg/100g vegetable material (P3) was the best result with absolute weight growth (1.49 g), absolute length growth (2.48 cm), feed efficiency (79.44%), protein efficiency ratio (2.03%), and survival (100%).